Images of aging in institutionalized and non-institutionalized elderly people - Lopes, Marlene (2012)
Aim: The aim of this study was to assess and compare images and stereotypes of aging in institutionalized and non-institutionalized elderly people. This is a descriptive study using a survey. Method: The instruments used were a sociodemographic questionnaire and the ImAges scale. A total of 120 elderly people, aged between 65 and 99 years, participated in this study. Results: Statistically significant differences were found, for the scale’s three factors, between institutionalized and non-institutionalized older adults. In the factor “dependence, sadness and old-fashioned”, the institutionalized participants presented a higher number of negative images and stereotypes (M = 51.8; DP = 6.01) than the non-institutionalized participants (M = 49.0; DP = 7.85), these differences were significant (t(118) = -2.16; p < 0.05). In the “maturity, activity and affectivity” factor, there were also significant differences (t(118) = 2.04; p < 0.05), the non-institutionalized participants present higher rates of positive images and stereotypes (M = 20.2; DP = 3.28), when compared to institutionalized participants (M = 19.0; DP = 3.310). Conclusion: The results suggested that institutionalized older adults presented more negative aging images than non-institutionalized.